Dire straits : the perils of writing the early modern English coastline from Leland to Milton - Bellamy, Elizabeth J. (Elizabeth Jane) (University of Toronto Press, 2013)
By illustrating how early modern English writers created their works in the context of a longstanding cultural inheritance from antiquity, Elizabeth Jane Bellamy offers a new approach to the history of early modern cartography and its influences on literature.